Social Media in Teaching-Learning Process: Investigation of the Use of Whatsapp in Teaching and Learning in University of Port Harcourt - Abraham, Oriji; Fanny, Anikpo (European Scientific Journal, ESJ, 2019)
There is no doubt that digital technologies play major roles in education inmodern times. Whatsapp mobile technology has been of immense value in this respect, as it is frequently and globally used in online instruction in universities. As well, it offers students increased choices and opportunities in the context of online instruction. Consequently, the purpose of this research work is to find out exactly to what extent the students and lecturers in the University of Port Harcourt, Faculty of Education are using the Whatsapp instant messaging tool in teaching and learning process in Faculty of Education, University of Port Harcourt, Nigeria. It also tried to find out if the aforesaid have enabling phones that are Internet ready to utilize the Whatsapp software in teaching and learning process. It attempts to discover major challenges, if any that are confronting its effective application in teaching and learning. Descriptive survey approach was adopted. The population for the study comprised of one hundred and twenty-eight (128) lecturers and one thousand six hundred and three (1603) first year undergraduate students of the University of Port Harcourt, Faculty of Education for the year 2017. Three (3) research questions guided the study. The research instrument used was a- 12 item questionnaire for both lecturers and the students correspondingly. It was validated with a reliability index of 0.70 and considered appropriate for the study. The researchers also employed an in-depth interview method to cover any discrepancy in the structured questionnaire, which was administered to the lecturers and the students respectively. The research questionnaires so retrieved from both respondents were analyzed, using statistical percentile to answer the necessary research questions. The results revealed that regardless of the fact that both the lecturers and the students possess Internet enabled mobile phones, they were not properly utilizing Whatsapp instant messaging for effective academic activities because only 15(11.7%) of lecturers and 243(22.9%) of students actually use it for academic purposes. The result further revealed that 100% of both lecturers and students never received any form of training for the use of Whatsapp mobile technology. Recommendations were also made, which included among others, adequate training on Whatsapp skills and the purchase of Internet enabled phones for effective utilization of Whatsapp instant messaging in teaching and learning process.